2020
DOI: 10.22541/au.159430767.74823064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Right Atrial Volume Index to Left Atrial Volume Index Ratio is Associated with Adverse Clinical Outcomes in Cardiogenic Shock

Abstract: Background: Structural remodeling in chronic systolic heart failure (HF) is associated with neurohormonal and hemodynamic perturbations among HF patients presenting with cardiogenic shock (CS) and HF. Objectives: To test the hypothesis was that atrial remodeling marked by an increased right atrial volume index (RAVI) to left atrial volume index (LAVI) ratio is associated with adverse clinical outcomes in CS. Methods: Patients included were admitted to the intensive care unit with evidence of congestion (pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…PH has been associated with adverse outcomes in many cardiovascular conditions 23 . On the other hand, RLR is also associated with adverse outcomes in patients with PH, 24 cardiogenic shock, 8 and in hospital cardiac arrest 9 . Studies have demonstrated the independent association of PH with adverse outcomes following TMVr 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PH has been associated with adverse outcomes in many cardiovascular conditions 23 . On the other hand, RLR is also associated with adverse outcomes in patients with PH, 24 cardiogenic shock, 8 and in hospital cardiac arrest 9 . Studies have demonstrated the independent association of PH with adverse outcomes following TMVr 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Structural changes in atrial dimension/volumes are often a reflection of pressure and volume changes occurring in the ventricles. It has been previously shown that increased right to left atrial volume indices (RAVI and LAVI) portends worse outcomes in patients with pulmonary hypertension (PH), 8 cardiogenic shock, 8 and in hospital cardiac arrest 9 . LAVI in particular is gaining recognition as an indicator of overall cardiac function, and has been termed “the HbA1c of the heart.” 10 There is limited evidence regarding the prognostic implications of RAVI and LAVI in patients undergoing TMVr.…”
Section: Introductionmentioning
confidence: 99%